Current Trend of Prescribing Anticoagulant and Antiviral Drugs in the Treatment of COVID- 19 Patients in a Corona Dedicated Hospital in Khulna (Mediscope, 2023)
Background: Thrombo-embolic incidence secondary to COVID-19 with increased mortality rate has become a global concern. Anticoagulants are widely used to prevent mortality. On the other hand, antiviral therapy has a potential effect against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).Aims & objectives: This study aims to assess the use pattern of anticoagulant and antiviral drugs against COVID-19.Methods: This is an observational cross-sectional study where two hundred COVID-19-positive patients of both sexes and different age groups who received anticoagulants and antivirals were recruited. All data were compiled in a Microsoft excel spreadsheet. Results were expressed in frequency & percentage.Results: Out of 200 patients, there were 115 males (57.5%) & 85 females (42.5%); the majority (56%) belonged to the age group between 30 to 60 years. Clinically, patients were categorized into mild (25%), moderate (32%), severe (37.5%), and critical (5.5%) cases. In this study, 88% of patients received low molecular weight heparin (enoxaparin) in a prophylactic dose and 12% of patients received in a therapeutic dose. Among the antivirals, remdesivir (84%) followed by favipiravir (16%) were the most commonly prescribed drugs.Conclusion: Anticoagulant (enoxaparin) and antiviral (remdesivir) drugs are frequently prescribed in the treatment of COVID-19 patients.Mediscope 2023;10(1):10-16